A new form of hazardous microparticulate contamination to the marine environment from ships using heavy fuel oil with exhaust gas scrubbers – Characterization and implications for fate, transport and ecotoxicity - Gondikas, Andreas; Mattsson, Karin; Hassellöv, Martin (The Science of the total environment, 2025)
Aiming to reduce sulfur oxides emission in the atmosphere, the International Maritime Organization developed regulations on shipping that came into effect in 2020. The new rules incentivized many owners to install scrubber systems on thousands of ships. However, the overall environmental implications of scrubbers is a controversial subject, largely due to the release of acids, metals, and chemicals in the oceans and impact on marine life. In order to close some of the knowledge gaps on the role and characteristics of these contaminants, we determine the physicochemical properties of the particulate fraction of scrubber effluent from four ships, with a complementary set of analytical techniques. We find that scrubber effluent contains particles in the order of 108 per liter, with diverse properties. Focusing on particles larger than 10 μm in diameter, we find that approximately 10 % will accumulate on the water surface according to particle size and density, while the rest will settle on sediments at velocities ranging from 1 to 9 m/d. Chemical analysis shows that particle composition is also diverse and depends on fuel oil, engine type and loading, scrubber configuration, and post-scrubber treatment. Particles are enriched with PAHs, sulfur, vanadium, iron, nickel, chromium, and titanium. Interestingly, we found carbon-rich microparticles aggregated with multiple metal-rich nanoparticles, whose transport behavior will be determined by the larger and less dense microparticles, but their toxicity will be driven by the metal-bearing nanoparticles and PAHs concentration. [Display omitted] •Scrubber effluent is often perceived as a homogeneous liquid waste; it is not.•Particles in scrubber effluent act as carriers of metals and polycyclic aromatic hydrocarbons.•The majority of particles from scrubber effluent will accumulate in the sediments.•Particle properties depend on fuel type, engine load, and operation conditions.•Scrubbers are effectively transferring hazardous pollution from air to seawater.